Organophosphorus Poisoning with Homicidal Intention in a Neonate - Laxman Basany; Roja Aepalapala (JCDR Research and Publications Pvt. Ltd., 2022)
Organophosphorus Compounds (OPC) are widely used as pesticides, and poisoning due to OPC is very rare in neonates. A 12-day- old female neonate was admitted with gasping respiration, excessive oral secretions and cold extremities. She had frothing from mouth and nose with an offensive odour, was hypothermic, hypotonic, cyanosed and was in mild stupor. Pupils were pin pointed, capillary refill time was 4-5 sec and had bilateral crepitations of lungs on auscultation. The baby was intubated, given 0.1 mg of atropine followed by 0.9% saline bolus and gastric lavage. She was treated with empirical antibiotics, atropine, Pralidoxime (PAM) and respiratory support. The baby responded well to treatment and was discharged on 10th day of admission. This could be the second case of Organophosphorus (OP) poisoning with homicidal intention reported in neonates.